Mycoplasma Protocols - Miles, Roger J.; Nicholas, Robin A. J.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1998)
In Mycoplasma Protocols, Roger Miles and Robin Nicholas present a collection of cutting-edge methods for the detection, isolation, identification, characterization, and genetic manipulation of the pathogenic mycoplasmas. These step-by-step methods are crafted for successful reproducibility and include biochemical, genetic, and molecular techniques essential to understanding pathogenicity and adhesion to host cells. They also cover the detection of mycoplasmas in cell cultures, an important tool not only in viral diagnosis and research, but also in the production of vaccines and various biological products. Mycoplasma Protocols provides up-to-date and easy-to-follow mycoplasma methods for practical application in medical and veterinary diagnostic and research laboratories. The techniques permit effective work with these normally fastidious microorganisms, allowing investigators to illuminate their roles across a wide range of chronic respiratory, arthritic, and urogenital diseases. For all those working in this important field, Mycoplasma Protocols immediately becomes the methodological resource of choice.
Medical Significance of Mycoplasmas -- The Veterinary Significance of Mycoplasmas -- Recovery of Human Mycoplasmas -- Recovery of Mycoplasmas from Animals -- Recovery of Mycoplasmas from Birds -- Cultivation of Ureaplasmas -- Quality Control Testing of Mycoplasma Medium -- Biochemical Characteristics in Mycoplasma Identification -- Enzyme Analysis -- Determination of Substrate Utilization Rates by Mycoplasmas -- Serological Identification of Mycoplasmas by Growth and Metabolism Inhibition Tests -- Identification of Mycoplasmas by Dot Immunobinding on Membrane Filtration (MF Dot) -- Identification of Mycoplasmas by Immunofluorescence -- Diagnostic Application of Monoclonal Antibody (MAb)-Based Sandwich ELISAs -- Immunohistochemical Staining of Fixed Tissues -- Extraction of DNA from Mycoplasmas -- Characterization of Mycoplasmas by PCR and Sequence Analysis with Universal 16S rDNA Primers -- PCR and RFLP Methods for the Specific Detection and Identification of Mycoplasma mycoides subsp. mycoides SC -- Characterization of Mycoplasmas by RAPD Fingerprinting -- Classification of Isolates by DNA-DNA Hybridization -- Insertion Sequence Analysis -- Detection of Mycoplasmas in Cell Cultures by Cultural Methods -- Detection of Mycoplasmas in Cell Culture by Fluorescence Methods -- Transformation of Mycoplasmas -- Transposon Mutagenesis -- Demonstration of Extrachromosomal Elements -- Expression of Foreign Genes in Acholeplasma laidlawii -- Mycoplasma Gene Expression in Escherichia coli -- Polyacrylamide Gel-Electrophoresis Separation of Whole-Cell Proteins -- Immunological and Biochemical Characterization of Membrane Proteins -- Detection and Analysis of Mycoplasma Adhesins -- Transmission Electron Microscopy and Immunogold Staining of Mollicute Surface Antigens.
Keywords: Microbiology; Microbiology